2008
DOI: 10.1063/1.2964114
|View full text |Cite
|
Sign up to set email alerts
|

Structural, optical, and electrical properties of epitaxial titanium oxide thin films on LaAlO3 substrate

Abstract: Articles you may be interested inEffect of SnO2 concentration on the tuning of optical and electrical properties of ZnO-SnO2 composite thin films Electrical and optical properties of transparent conducting In4+xSn3−2xSbxO12 thin films J. Appl. Phys. 110, 033702 (2011); 10.1063/1.3605552Structure-related optical properties of ( Pb , La ) ( Zr , Ti ) O 3 thin films on indium tin oxide∕quartz substrates Titanium oxide thin films were prepared by pulsed-laser deposition on LaAlO 3 single crystal substrate at 700°C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 35 publications
1
9
0
Order By: Relevance
“…3͑a͒. The TiO 2 layers are found to have epitaxial orientation relationships ͑001͒ TiO 2 ʈ ͑001͒ LAO and ͓100͔ TiO 2 ʈ ͓100͔ LAO with substrate, in accordance with previous reports 16,40 and the above XRD analyses demonstrating strongly ͑001͒-oriented textures for both materials.…”
Section: B Interfacial Orientation Relationships and Microstructuressupporting
confidence: 91%
“…3͑a͒. The TiO 2 layers are found to have epitaxial orientation relationships ͑001͒ TiO 2 ʈ ͑001͒ LAO and ͓100͔ TiO 2 ʈ ͓100͔ LAO with substrate, in accordance with previous reports 16,40 and the above XRD analyses demonstrating strongly ͑001͒-oriented textures for both materials.…”
Section: B Interfacial Orientation Relationships and Microstructuressupporting
confidence: 91%
“…Regarding XRD patterns, these differences could be explained by a better crystalline quality in R 200 rather than in R PC as the FWHM of (2 0 0) peak of R-TiO 2 is smaller than the other ones. In previous works [17,18], it has been demonstrated that R-or A-TiO 2 films grown on sapphire and LaAlO 3 substrates are strongly oriented according to the same out-of plane relationships evidenced in the present study and they are also epitaxied allowing for such films to be almost considered as like-single crystal. Despite its interesting structural properties, the A-TiO 2 films do not lead to intense PL emission due to the STE process.…”
Section: Effect Of Dopant Concentration On Integrated Photoluminescenmentioning
confidence: 81%
“…Indeed, the flux of oxygen atoms reaching the surface of the growing film depends upon the oxygen partial pressure (PO 2 ) in the ablation chamber and, consequently, the incorporation of oxygen atoms in oxide films may be strongly limited when PO 2 is decreased as it has been recently reported on the growth of oxygen deficient perovskite phase [12,13] or oxygen deficient titanium oxide [14,15]. In addition, the incorporation of oxygen in films may be increased by using an external source of plasma.…”
Section: Phases and Crystallite Orientationsmentioning
confidence: 99%